2018
DOI: 10.3390/biom8020026
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Remodeling as a Key Player of the Hepatotoxicity Induced by Co-Exposure to Benzo[a]pyrene and Ethanol of Obese Zebrafish Larvae

Abstract: The rise in prevalence of non-alcoholic fatty liver disease (NAFLD) constitutes an important public health concern worldwide. Including obesity, numerous risk factors of NAFLD such as benzo[a]pyrene (B[a]P) and ethanol have been identified as modifying the physicochemical properties of the plasma membrane in vitro thus causing membrane remodeling—changes in membrane fluidity and lipid-raft characteristics. In this study, the possible involvement of membrane remodeling in the in vivo progression of steatosis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 107 publications
2
16
0
Order By: Relevance
“…Various studies have shown that high levels of air pollutants including benzo(a)pyrene are linked with many adverse clinical complications comprising various organ injuries such as lungs, liver, and kidneys with increased mortality as well as morbidity [9,12,18,19]. However, the mechanisms accountable for such association have not been fully explained; few studies showed increased oxidative stress, inflammation, apoptosis, and impairment of cell cycle was due to exposure tobenzopyrene.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that high levels of air pollutants including benzo(a)pyrene are linked with many adverse clinical complications comprising various organ injuries such as lungs, liver, and kidneys with increased mortality as well as morbidity [9,12,18,19]. However, the mechanisms accountable for such association have not been fully explained; few studies showed increased oxidative stress, inflammation, apoptosis, and impairment of cell cycle was due to exposure tobenzopyrene.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent investigations of different experimental models of MAFLD suggested that benzo[a]pyrene exposure might even further aggravate the progression of steatosis to steatohepatitis induced by ethanol [176,[213][214][215]. Potential mechanisms involved in such progression include overproduction of ROS and nitric oxide [176,214], mitochondrial dysfunction [176], increased expression of proinflammatory cytokines [213] and plasma membrane remodeling [215].…”
Section: Ethanolmentioning
confidence: 99%
“…Also, FluvaSt inhibited Fcγ receptor signaling in monocyte rafts, which was rescued by mevalonate, whereas the use of prenyl transferase inhibitors was without effect, thus indicating the involvement of these cholesterol-rich membrane domains [ 81 ]. Finally, PravaSt (at the low concentration of 0.5 μM) counteracted the deleterious effect of exposure to benzo( a )pyrene and ethanol of hepatic cells and of obese zebrafish larvae liver, which was mediated by membrane remodeling altering cholesterol-containing rafts that mediate inflammatory signaling [ 82 ].…”
Section: In-vitro Effects Of Statins On Cholesterol-enriched Membrane Microdomains: Rafts Can Be Altered By Statinsmentioning
confidence: 99%